2017
DOI: 10.5812/modernc.65664
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Risk Factors of Type II Diabetes Mellitus Among Patients with Hepatitis B Virus: A Descriptive Correlational Study

Abstract: Background: There are 350 million carriers of hepatitis B virus (HBV) around the world. HBV can be associated with type II diabetes mellitus. The aim of this study was to evaluate the prevalence and risk factors for type II diabetes mellitus among patients with HBV. Methods: This community-based, cross sectional, descriptive, correlational study recruited participants above 13 years, who resided in Esfandiar rural area, Tabas, Iran. A blood sample was collected from each participant for serological and biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Caronia et al (19) and Ozylikan et al (20) proved the high prevalence of diabetes mellitus in patients with hepatitis C. Drakoulis (2002) and Chern (2001) showed that chronic hepatitis C infection could have a diabetogenic effect because hepatitis C increases liver damage caused by the accumulation of excess iron in the liver, and the developed liver dysfunction can be a factor in insulin resistance and impaired glucose tolerance (21,22). A study conducted by Ebrahimzadeh in Esfandiare proved that the prevalence of HBsAg in diabetics was higher than that in non-diabetics (23). These differences can be due to the limited sample size of the current study and the differences in the race and geographical distribution or overall incidence of diabetes mellitus in each region, and also different demographic variables, and even the type of tests and kits.…”
Section: Discussionmentioning
confidence: 99%
“…Caronia et al (19) and Ozylikan et al (20) proved the high prevalence of diabetes mellitus in patients with hepatitis C. Drakoulis (2002) and Chern (2001) showed that chronic hepatitis C infection could have a diabetogenic effect because hepatitis C increases liver damage caused by the accumulation of excess iron in the liver, and the developed liver dysfunction can be a factor in insulin resistance and impaired glucose tolerance (21,22). A study conducted by Ebrahimzadeh in Esfandiare proved that the prevalence of HBsAg in diabetics was higher than that in non-diabetics (23). These differences can be due to the limited sample size of the current study and the differences in the race and geographical distribution or overall incidence of diabetes mellitus in each region, and also different demographic variables, and even the type of tests and kits.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 20 (12,13,14,15,16,17,18,19,21,22,23,24,25,26,27,28,29,30,31,32) studies were analyzed with 245,468,411 subjects were enrolled this study which were published between 2003 to 2020. In which divided into two subgroups, 12,982,158 patients with HBV infected group and 232,486,253 patients in non infected HBV groups.…”
Section: Figure 2 Outlines the Characteristics Of Included Studiesmentioning
confidence: 99%